STUDI TENTANG PENERAPAN ADMINISTRASI PERENCANAAN DAN PENGENDALIAN PRODUKSI PADA PT SANWA ENGINEERING BATAM - Putrhi Pranitha Napitu; Dwi Kartikasari (Politeknik Negeri Batam, 2017)
This study aims to develop operational standards of administrative procedures of production planning and control in PT Sanwa Engineering Batam. Methods of data collection using method of documentation and structured interview to planner and customer service planner. While for data analysis using descriptive qualitative analysis and also SWOT analysis (Strengths, Weakness, Opportunity, and Threats) which discuss about how application of planning and controlling production at PT Sanwa Engineering Batam start from production planning, production scheduling, production supervision, related organizational functions and information and documents required. The results of this research is the formation of a flowchart of the administration process of planning and controlling new production in more detail so as to facilitate new employees to understand their work or the reader understand the principal activities of a staff of administration in the production department.